2014
DOI: 10.1016/j.tranon.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-196a and -196b as Potential Biomarkers for the Early Detection of Familial Pancreatic Cancer

Abstract: Screening programs are recommended for individuals at risk (IAR) from families with familial pancreatic cancer (FPC). However, reliable imaging methods or biomarkers for early diagnosis of pancreatic ductal adenocarcinoma (PC) or its precursor lesions are still lacking. The ability of circulating microRNAs (miRNAs) to discriminate multifocal high-grade precursor lesions or PC from normal was examined. The presence of miRNA-21, -155, -196a, -196b and -210 was analyzed in the serum of transgenic KPC mice to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 44 publications
0
62
0
Order By: Relevance
“…Consistent with previous studies [22,23], we found that miR-21-5p and miR-155 were abnormally expressed in PDAC tissues and precursor lesions. In addition, miR196b, miR-145, miR-217, and miR-148a also underwent remarkable changes in PanINs [24][25][26], suggesting that these miRNAs may be novel biomarkers to detect PDAC at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies [22,23], we found that miR-21-5p and miR-155 were abnormally expressed in PDAC tissues and precursor lesions. In addition, miR196b, miR-145, miR-217, and miR-148a also underwent remarkable changes in PanINs [24][25][26], suggesting that these miRNAs may be novel biomarkers to detect PDAC at early stages.…”
Section: Discussionmentioning
confidence: 99%
“…Further, expression of these miRNAs were significantly higher in the serum of PC patients with sporadic/hereditary or individuals at risk (IAR) with multifocal PanIN2/3 lesions compared to patients with neuroendocrine pancreatic tumors or chronic pancreatitis, IAR with PanIN1 or no PanIN lesions and healthy controls with a sensitivity of 100% and specificity of 90% (AUC = 0.99). However, it was observed only in few samples, therefore, further validation of miR-196a and -196b should be carried out to test their utility in PC diagnosis [230]. A meta-analysis study was carried out on 18 articles with a total of 2,036 patients and 1,444 controls to determine the role miRNAs in early diagnosis and reported that pooled sensitivity of 82 % (95 % CI, 78–86 %); and specificity of 77 % (95 % CI, 73–81 %) with AUC of 0.86 (95 % CI, 0.83–0.89), suggesting the potential diagnostic value of miRNAs (inclusion of multiple miRNAs for diagnosis) to discriminate PC patients from healthy controls with high sensitivity and specificity [231].…”
Section: Potential Role Of Mirnas In Pancreatic Cancer Diagnosismentioning
confidence: 99%
“…The funding genes or oncogenic genes in cancer tumorigenesis as well as in gastric cancer (Shenouda and Alahari, 2009;Bartels and Tsongalis, 2010;Cortes-Sempere and Ibanez de Caceres, 2011). Mir-196a is a newly reported miRNA biomarkers relevant to multiple cancers, such as breast cancer (Lee et al, 2014), lung cancer , cervical cancer (Gocze et al, 2013), renal cancer (Du et al, 2014a), head and neck cancer (Christensen et al, 2010), hepatocellular cancer (Hao et al, 2013), pancreatic cancer (Slater et al, 2014), colorectal cancer (Zhan et al, 2011;Du et al, 2014b) and early gastric cancer (Zheng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%